Habeas Corpus: poczucie własności swojego ciała - Frederique de Vignemont (Avant, 2012)
What grounds my experience of my body as my own? The body that one experiences is always one’s own, but it does not follow that one always experiences it as one’s own. One might even feel that a body part does not belong to oneself despite feeling sensations in it, like in asomatognosia. The article aims at understanding the link between bodily sensations and the sense of ownership by investigating the role played by the body schema.